2019
DOI: 10.2147/dddt.s216156
|View full text |Cite
|
Sign up to set email alerts
|

<p>Rutaecarpine may improve neuronal injury, inhibits apoptosis, inflammation and oxidative stress by regulating the expression of ERK1/2 and Nrf2/HO-1 pathway in rats with cerebral ischemia-reperfusion injury</p>

Abstract: BackgroundCerebral ischemia-reperfusion (CI/R) injury is a more serious brain injury caused by the recovery of blood supply after cerebral ischemia for a certain period of time. Rutaecarpine (Rut) is an alkaloid isolated from Evodia officinalis with various biological activities. Previous studies have shown that Rut has a certain protective effect on ischemic brain injury, but the specific molecular mechanism is still unknown.MethodsIn this study, a rat model of CI/R was established to explore the effects and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…These enzymes can resist oxidative stress and damage produced by various internal and external stimuli, and promote the return to equilibrium of oxygen free radicals. Certain drugs and naturally extracted compounds (sulforaphane, ginkgo extract, white squash, andrographolide derivative CX-10, rutaecarpine, ginsenoside Rg1, and levocarnitine, among others) are able to protect the body from stroke damage by activating the Nrf2 signaling pathway (Alfieri et al, 2013;Chu et al, 2019;Han et al, 2019;Liu and Zhang, 2019;Yang et al, 2019). In vitro, activated Nrf2 has strong neuroprotective properties and can inhibit stroke injury mechanisms such as glutamate toxicity, H 2 O 2 exposure, and Ca 2+ overloading (Xu P. et al, 2018).…”
Section: Anti-oxidative Stress Signal Pathway Nrf2/are Signaling Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…These enzymes can resist oxidative stress and damage produced by various internal and external stimuli, and promote the return to equilibrium of oxygen free radicals. Certain drugs and naturally extracted compounds (sulforaphane, ginkgo extract, white squash, andrographolide derivative CX-10, rutaecarpine, ginsenoside Rg1, and levocarnitine, among others) are able to protect the body from stroke damage by activating the Nrf2 signaling pathway (Alfieri et al, 2013;Chu et al, 2019;Han et al, 2019;Liu and Zhang, 2019;Yang et al, 2019). In vitro, activated Nrf2 has strong neuroprotective properties and can inhibit stroke injury mechanisms such as glutamate toxicity, H 2 O 2 exposure, and Ca 2+ overloading (Xu P. et al, 2018).…”
Section: Anti-oxidative Stress Signal Pathway Nrf2/are Signaling Pathwaymentioning
confidence: 99%
“…In theory, blocking pathways or targeting the key molecules of ROS generation can reduce the oxidative damage caused by CIRI. Some progress has been made in antioxidant treatments for CIRI (Kim et al, 2009;Hu et al, 2013;Watanabe et al, 2016;Mahmood et al, 2017;Lou et al, 2018;Song et al, 2018;Xing et al, 2018;Zhu et al, 2018;Chu et al, 2019;Han et al, 2019;Li S. et al, 2019;Liu and Zhang, 2019).…”
Section: Antioxidant Therapy In Cirimentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, NRF2-dependent antioxidant and detoxification enzymes promote the detoxification and elimination of ROS to attenuate arsenic carcinogenesis. On the other hand, NRF2 activation may provide cell proliferation or survival advantage by mediating metabolic reprogramming [56,97] and contributing to apoptotic resistance [98][99][100][101], which are important events in the process of arsenic-induced malignant transformation. Long-term exposure to an environmentally relevant dose of arsenic may induce constitutive activation of Nrf2, leading to adaptive antioxidant response, and subsequently contributing to malignant transformation [60,74,102,103].…”
Section: Nrf2-are Pathwaymentioning
confidence: 99%
“…Therefore, understanding the specific mechanisms underlying reperfusion injury is of clinical importance. Numerous studies have demonstrated that inflammation is an important pathological factor contributing to CIRI (4)(5)(6). It has also been reported that a particular type of proinflammatory programmed cell death, pyroptosis, also serves an important role in the pathogenesis of I/R injury (7).…”
Section: Introductionmentioning
confidence: 99%